Pelvic Organ Distribution of Mesenchymal Stem Cells Injected Intravenously after Simulated Childbirth Injury in Female Rats - Michelle Cruz; Charuspong Dissaranan; Anne Cotleur; Matthew Kiedrowski; Marc Penn; Margot Damaser (Obstetrics and Gynecology International)
The local route of stem cell administration utilized presently in clinical trials for stress incontinence may not take full advantage of the capabilities of these cells. The goal of this study was to evaluate if intravenously injected mesenchymal stem cells (MSCs) home to pelvic organs after simulated childbirth injury in a rat model. Female rats underwent either vaginal distension (VD) or sham VD. All rats received 2 million GFP-labeled MSCs intravenously 1 hour after injury. Four or 10 days later pelvic organs and muscles were imaged for visualization of GFP-positive cells. Significantly more MSCs home to the urethra, vagina, rectum, and levator ani muscle 4 days after VD than after sham VD. MSCs were present 10 days after injection but GFP intensity had decreased. This study provides basic science evidence that intravenous administration of MSCs could provide an effective route for cell-based therapy to facilitate repair after injury and treat stress incontinence.